Economics of Watershed Management - Chakravarty, M.K. (Journal of Soil and Water Conservation, 2022)
Land, Soil, Water, Minerals and Forest etc. constitute the principal natural resources. Of these land, soil and water are nearest to mankind and to the rural community. In nature there is a balance between the slow production of top soil and its slow removal. Increase in human and cattle population, improper handling and interference of the natural resources have brought the ecological imbalance for which conservation of soil and water has been felt necessary.